Quantification of Optical Coherence Tomography Angiography in Age and Age-Related Macular Degeneration Using Vessel Density Analysis. Issue 2 (March 2020) - Vaghefi, Ehsan; Hill, Sophie; Kersten, Hannah M.; Squirrell, David
Abstract : Purpose: The aim of this study was to determine whether vessel density (VD) as measured by optical coherence tomography (OCT) angiography provided insights into retinal and choriocapillaris vascular changes with aging and intermediate dry age-related macular degeneration (AMD). Design: Non-randomized observational study. Methods: Seventy-five participants were recruited into 3 cohorts: young healthy group, old healthy, and those at high-risk for exudative AMD. Raw OCT and OCT angiography data from TOPCON DRI OCT Triton were exported using Topcon IMAGENET 6.0 software, and 3D datasets were analysed to determine retinal thickness and VD. Results: Central macular thickness measurements revealed a trend of overall retinal thinning with increasing age. VD through the full thickness of the retina was highest in Early Treatment Diabetic Retinopathy Study (ETDRS) sector 4 (the inferior macula) in all the cohorts. Mean VD was significantly higher in the deep capillary plexus than the superficial capillary plexus in all ETDRS sectors in all cohorts, but there was no significant difference noted between groups. Choriocapillaris VD was significantly lower in all ETDRS sectors in the AMD group compared with the young healthy and the old healthy groups. Conclusions: Retinal VD maps, derived from the retinal plexi, are not reliable biomarkers for assessing the aging macular. Our nonproprietary analysis of the vascular density of the choriocapillaris revealed a significant drop off of VD with age and disease, but further work is required to corroborate this finding. If repeatable, choriocapillaris VD may provide a noninvasive biomarker of healthy aging and disease.